2006
DOI: 10.1007/s00104-006-1194-3
|View full text |Cite
|
Sign up to set email alerts
|

Neues in der perioperativen antibiotischen Prophylaxe

Abstract: Perioperative antimicrobial prophylaxis (PAP) leads to a reduction in surgical site infections. The aim of PAP is adequate serum and tissue concentrations of the antimicrobial drug in the field of operation. The antibiotic must be effective against the expected pathogens during the operation, safe, and have the fewest possible side effects. The indication for PAP should take into account the risks of the operative procedure and especially the individual risk factors of the patient. Depending on pharmacokinetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
3

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 46 publications
(32 reference statements)
0
7
0
3
Order By: Relevance
“…When combined, such drugs may share a common adverse effect that is clinically insignificant when each drug is given separately. Local anesthetics can be used regionally or intravenously for perioperative pain control, and to prevent surgical site infection, antibiotics are administered before anesthesia [1]. In the perioperative period, some patients may receive combinations of therapeutic doses of the above drugs as well as a neuromuscular (NM) blocker.…”
Section: Introductionmentioning
confidence: 99%
“…When combined, such drugs may share a common adverse effect that is clinically insignificant when each drug is given separately. Local anesthetics can be used regionally or intravenously for perioperative pain control, and to prevent surgical site infection, antibiotics are administered before anesthesia [1]. In the perioperative period, some patients may receive combinations of therapeutic doses of the above drugs as well as a neuromuscular (NM) blocker.…”
Section: Introductionmentioning
confidence: 99%
“…Because many antibiotics are administered 60 minutes before surgical incision to prevent surgical site infection [1], perioperative antimicrobials are typically administered before anaesthesia. Anaesthesiologists are often responsible for the administration of antibiotics in the preoperative and intraoperative periods; however, they may be unfamiliar that the administration of antibiotics is associated with the potentiation of neuromuscular blocking (NMB) agents [2].…”
Section: Introductionmentioning
confidence: 99%
“…Clindamycin has typically been used to treat infections that are caused by anaerobic and aerobic bacteria other than enterococci [1]. In addition to having antibacterial effects, clindamycin produces an open ion channel block on the end-plate [7,8] and decreases acetylcholine release at the motor nerve terminal [9], thus, prolonging or enhancing neuromuscular block that is caused by nondepolarizing NMB drugs [10-14].…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, two large prospective studies observed the lowest risk of SSI when SAP was given within 30 minutes prior to incision, and the National Surgical Infection Prevention Project simply recommends administering SAP as close to the incision time as possible [51-53]. Similar statements are made in European guidelines [54,55]. …”
Section: Introductionmentioning
confidence: 94%